2019
DOI: 10.1002/qua.25979
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of different coumarin donors on the optical and photovoltaic properties of azo‐bridged push‐pull systems: A theoretical approach

Abstract: We report the theoretical modeling of various azo-bridged coumarin-purpurin systems. The effect of varying the donor (coumarin) part of this D-π-D-π-A system was analyzed in terms of opto-electronic and photovoltaic parameters such as HOMO, LUMO, HOMO-LUMO energy gap, λ max , light harvesting efficiency, charge injection efficiency, open voltage, reorganization energy by employing density functional theory as incorporated in Gaussian 03 set of codes. The dye-TiO 2 adsorbed systems were also studied using the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 109 publications
(150 reference statements)
0
23
0
Order By: Relevance
“…The light‐harvesting ability, LHE , of the dyes is evaluated by Equation : italicLHE=110boldf where f is the oscillator strength. Electron driving force, eV OC , of the studied pigments, is also evaluated according to Equation : eVOC=EitalicLUMO()dyeEitalicCB()italicTiO2 …”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The light‐harvesting ability, LHE , of the dyes is evaluated by Equation : italicLHE=110boldf where f is the oscillator strength. Electron driving force, eV OC , of the studied pigments, is also evaluated according to Equation : eVOC=EitalicLUMO()dyeEitalicCB()italicTiO2 …”
Section: Computational Detailsmentioning
confidence: 99%
“…The first dye‐sensitized solar cell (DSSC) was improved by O'Regan and Grätzel . DSSCs are engaging due to their low‐cost synthesis, working capability under the light conditions, and tunable transparency …”
Section: Introductionmentioning
confidence: 99%
“…[16] Some efficient push-pull systems, such as azo-bridged coumarin-purpurin based systems (CM1-CM7) were studied. [17] On the basis of the results, the substitution of the donor moiety (coumarin) and solvent affect the optoelectronic and photovoltaic properties of the D-π-D-π-A systems. Among these dyes, CM6 was preferred because of a proper band gap, polarizability, spectroscopic behavior and light-harvesting efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the interaction of the dyes with (TiO 2 ) 6 showed that these dyes are efficient photosensitizers for DSSCs. [17] The influences of the chemical structure of the sensitizers on the photovoltaic properties were investigated. [17][18][19][20] For example, polypyridyl dyes based on Cr 2+ and V 3+ show better performance in comparison with ruthenium-and other scarce metal-based polypyridyl dyes due to the moderate LHE , high efficiencies of electron and hole injection, which make them promising alternatives to scarce Ru 2+ metal ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation